Yusuf al-Qaradawi: Memposisikan Sunnah Ghairu Tasyriiyah - Leli, Laili Zainab; Radifa Isnain Nafila (Mukaddimah: Jurnal Studi Islam, 2024)
This paper discusses the Sunnah of Ghayru Tasyriiyah which wa pioneered by sheikh Mahmud Syaltut which was later developed by Yusuf al-Qardhawi. This research is focused on answering the position of Sunnah Ghayru Tasyriiyah according to Yusuf al-Qardhwai. The research method used is literature where the source is obtained from books, journals, dictionaries and so on. This research is descriptive in nature and intends to explain or explain the position of Sunnah Ghayru tasyriiyahn according to Yusuf al-Qardhwi. Yusuf al-Qardhawi shows that the position of Sunnah Ghayru Tasyriiyah is sunnah which is not prescribed as obligatory sunnah and does not change it, but if it is in the form of an act the sunnah is only permisibble. On the other hand, apart from not being obligated and having been given to the people of the Sunnah, Ghayru Tasyriiyah is also not considered a permissible act according to the Shari’a, it is only permitted rationally in the form of the Sunnah actions it is only recommended, and if the form of orders and prohibitions only applies to sunnah and hadith related to the worldly.